Concentration, distribution, and correlation of heavy metals in seawater, sediment,and Cerithidea obtusa from coastal waters of Singkep Island, Riau Archipelago Province - Amin, Biotal; Nurrachmi, Irvina; ', Jamalus (Indonesian Journal of Environmental Science and Technology, 2014)
Concentration,  distribution  and  correlation  of  seven  heavy  metals  in  seawater,  sediment  and gastropod Cerithidea  obtusa from coastal waters in the proximity of abandoned tin mining in Singkep Island has been evaluated. Samples were taken from five stations and heavy metal analysis was carried out by using AAS Perkin Elmer 3110 in Marine Chemistry Laboratory Faculty of Fisheries and Marine Science University ofRiau. The mean concentrations  ofCd, Cu, Pb, Zn, Ni, Mn and Cr were 0.0373,  0.0776,  0.1340,  0.1692,01789,  0,1205  and  0.3232  mg/1 in  seawater;  2.0445,   11.5359,  24.6859,  23.7992,  13.2925,  13.1097  and79.0821  f.lg/g in sediment and 3.03, 69.71, 14.30, 120.73,  11.62, 56.29 and 18.75  J..lg/g in C. obtusa, respec tively. In general, the concentrations of metals in coastal water receiving effluents from abandoned tin mining activities in Singkep Island were higher than in coastal waters with less mining activities. Concentrations  of all those metals in seawater were positively correlated with sediment and  gastropod and its concentrations   in sediment  were  also  positively  correlated  with  those  in  gastropod.  Mean  concentration   of  all  metals  in sediment were still below the ERM values, except for Cd which was exceeded the ERL but  they were all still below the ERM  values.  Continuous  environment  monitoring  programs  should  be implemented  in Singkep Island coastal waters to evaluate possible increase of heavy metal threat as some new sand and bauxit mining activities are taking place.Key words: heavy metal, seawater, sediment, Cerithidea obtusa, mining